Design and Control of Nanoconfinement to Achieve Magnetic Resonance Contrast Agents with High Relaxivity. Issue 5 (22nd December 2015) - Malzahn, Kerstin; Ebert, Sandro; Schlegel, Isabel; Neudert, Oliver; Wagner, Manfred; Schütz, Gunnar; Ide, Andreas; Roohi, Farnoosh; Münnemann, Kerstin; Crespy, Daniel; Landfester, Katharina
Abstract : The enhanced relaxation of hydrogen atoms of surrounding water from suitable contrast agent promotes magnetic resonance imaging as one of the most important medical diagnosis technique. The key challenge for the preparation of performant contrast agents for magnetic resonance imaging with high relaxivity is to ensure a high local concentration of contrast agent while allowing a contact between water and the contrast agent. Both requirements are answered by tailoring a semipermeable confinement for a gadolinium complex used as contrast agent. A locally high concentration is achieved by successfully encapsulating the complex in polymer nanocontainers that serves to protect and retain the complex inside a limited space. The access of water to the complex is achieved by carefully controlling the chemistry of the shell and the core of the nanocontainers. The confinement of the nanocontainers enables an increased relaxivity compared to an aqueous solution of the contrast agent. The nanocontainers are successfully applied in vivo to yield enhanced contrast in magnetic resonance imaging. Abstract : The nanoconfinement of gadolinium complex provided by its encapsulation in nanocontainers allows for a significant increase of the relaxivity. Both core and shell of the nanocontainers are chemically tailored so that the retention of the complex and its relaxivity can be simultaneously optimized. The obtained nanocontainers are tested successfully in vivo.